Temporary Abdominal Wall Closure in Congenital Diaphragmatic Hernia by Bogota Bag Method - RaviKumar Ramanathan Valkodai (EL-Med-Pub, 2017)
In neonatal congenital diaphragmatic hernia (CDH) repair if the abdomen is closed with tension it poses the problem of abdominal compartment syndrome (ACS). In the index case with ACS, temporary closure of the abdomen was achieved with sterile urobag called the 'Bogota bag technique' with successful complete closure of abdomen after seven days. The other methods of temporary closure of the abdomen are discussed with emphasis on prevention of abdominal compartment syndrome. The ease and simplicity of the technique of urobag utilisation in such situation is outlined in the article.